(X-1)(y+3)=0

Simple and best practice solution for (X-1)(y+3)=0 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for (X-1)(y+3)=0 equation:



(X-1)(X+3)=0
We multiply parentheses ..
(+X^2+3X-1X-3)=0
We get rid of parentheses
X^2+3X-1X-3=0
We add all the numbers together, and all the variables
X^2+2X-3=0
a = 1; b = 2; c = -3;
Δ = b2-4ac
Δ = 22-4·1·(-3)
Δ = 16
The delta value is higher than zero, so the equation has two solutions
We use following formulas to calculate our solutions:
$X_{1}=\frac{-b-\sqrt{\Delta}}{2a}$
$X_{2}=\frac{-b+\sqrt{\Delta}}{2a}$

$\sqrt{\Delta}=\sqrt{16}=4$
$X_{1}=\frac{-b-\sqrt{\Delta}}{2a}=\frac{-(2)-4}{2*1}=\frac{-6}{2} =-3 $
$X_{2}=\frac{-b+\sqrt{\Delta}}{2a}=\frac{-(2)+4}{2*1}=\frac{2}{2} =1 $

See similar equations:

| -7v+21=2(v+6) | | 1m-2=6m-4 | | -49=7(-6u-1) | | -49=7(-3u-1) | | 4(u-4)=-8u+44 | | -49=7(10u-1) | | -49=7(u-1) | | 7-2=1-5x+2x | | -40=7(u-1) | | 7n-4n=6 | | 16=2(x+3)-7x | | W=1.5-0.12t | | -4x-4(-4x+8)=-104 | | -10+4x=5(x–2) | | 5x+6–4x=-4+3x-8 | | -8x-35=53 | | 2x-9+12=-7+3x | | 3+2(x–5)=12x | | 6(u-2)-3=-3(-9u+4)-9u | | 25x=31.50 | | 5k^2+5=-3 | | 5=(g-10)=45 | | 10x+24=6+16x | | 15/x=19 | | 25x=31.5 | | 3x+5x-2x-5=1 | | -3v-21=6(v+7) | | -2(2v-5)+4v=4(v+3) | | 15÷x=19 | | -21=-7w+3(w+5) | | 42=8x-14 | | 41=8x-14 |

Equations solver categories